Akumulasi logam berat (Pb dan Cu) pada Akar dan daun mangrove Avicennia marina di Sungai Lamong, Jawa Timur - Hikmah Farda Awaliyah; Defri Yona; Dwi Candra Pratiwi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2018)
Abstract. Mangrove ecosystem of Lamong River is located in an area with dense human activities such as industrial, heavy traffic, settlements and harbour activities. These activities could triggered the input of heavy metals, especially Pb and Cu. Mangrove ecosystem can be developed as a control of heavy metal pollution and also as a pollutant trap. In this study, the analysis of heavy metals (Pb and Cu) in water, sediment and mangorve’s roots and leaves were measured. The aim of this study was to determine the ability of Avicennia marina’s roots and leaves in absorbing heavy metals (Pb and Cu). Samples were obtained and then analysed by AAS (Atomic Absorbsion Spectrofotometer).The result showed that heavy metal concentrations of Pb were in the range of 0.11 mg/L - 16.87 mg/L and Cu in the range of 0.001 mg/L - 34.84 mg/L.Avicennia marina in the study site was categorized as excluder based on BCF1 and phytoextraction due to TF1. The results of this study indicate that Avicennia marina can be developed into phytoremidiation agents because they was able to absorb and transfer heavy metals from the environment to their plant tissues.Keywords: BCF; TF; Avicennia marina; Heavy metal; Lamong River Abstrak. Ekosistem mangrove Sungai Lamong terletak di area yang padat aktivitas manusia seperti aktivitas industri, lalu lintas yang padat, pemukiman dan pelabuhan. Hal tersebut memicu masukan logam berat, khususnya Pb dan Cu. Ekosistem mangrove dapat dikembangkan sebagai pengendalian pencemaran logam berat dan dapat juga digunakan sebagai pollutant trap. Pada penelitian ini bertujuan untuk mengetahui kemampuan Avicennia marinadalam menyerap logam berat Pb dan Cu dari lingkungannya. Sampel dianalisa menggunakan AAS (Atomic Absorbsion Spectrofotometer).Hasil konsentrasi logam berat Pb berkisar antara 0,11 mg/L – 16.87 mg/L dan Cu berkisar antara 0,001 mg/L – 34,84 mg/L. Avicennia marinadi lokasi penelitian bersifat excluderkarena nilai BCF1 dan fitoekstraksi karena nilai TF1. Hasil penelitian ini menunjukkan bahwa mangrove Avicennia marinadapat dikembangkan menjadi agen fitoremidiasi karena mampu menyerap dan mentransfer logam berat dari lingkungan ke jaringan tubuh yang lain.Kata kunci:BCF; TF; Avicennia marina; Logam berat; Sungai Lamong